Saw Sensor Properties at Elevated And Cyclic Temperature - Mohd Izham, Mohamad Khairul Zulfadly (Universiti Teknologi PETRONAS, 2014)
This project was conducted to obtain SAW sensor properties at elevated and cyclic temperature. The main objective is to apply certain range of temperature towards the SAW sensor. Amplitude and phase of the S parameter of the sensor then will be analyzed. S Parameters that will be focused on this project is S11 and S21 which are the reflection coefficient and tranmission coefficient. Variation of temperatures from 25⁰C to 100 ⁰C will be applied to the sensor in order to observe and analyze any changes in the amplitude and phase of the S21 and S11 parameters. The result shows that the properties of the sensor does not affected too much by the variance of temperatures. It can be concluded that the sensor can be functional at elevated and cyclic temperature without produce significance changes at the S21 and S11 parameters.